Pelaksanaan Pembelajaran Kelas Inklusi Bagi Siswa Tunagrahita di Kelas IV SDN Pataruman 2 Garut - Lia Safitri; Lutfi Asyari; Neni Nadiroti Muslihah (caXra: Jurnal Pendidikan Sekolah Dasar, 2023)
Now, the practice of inclusive education has not been optimally realized at the elementary school level in Garut Regency. This study aims to determine the implementation of inclusive class for mentally retarded student grade four at SDN Pataruman 2. The research method used descriptive qualitative. The research subjects were fourth grade teachers, inclusion coordinators, and fourth grade mentally retarded students at SDN Pataruman 2. The data were collected using observation, interview, and documentation techniques. The data obtained is then analyzed, the data is presented by drawing conclusions about the meaning of the data collected. The results showed that the teacher made special lesson plans, learning was carried out in class together, evaluation of special needs students used the same form as regular students. Special programs are planned and implemented at least once a month.